Opal glass cladding for side-emitting glass optical fibers, side-emitting glass optical fibers, and methods of making the same

CN122940358APending Publication Date: 2026-10-20SUZHOU YULIAN ZHIXING ENTERPRISE MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611026948.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

上述方法虽然能够产生侧向出光,但仍存在如下问题:一是散射颗粒位于纤芯时容易增加轴向传输损耗,导致传输距离缩短;二是外表面刻蚀或沉积工艺增加制造步骤,散射层与玻璃主体结合可靠性有限;三是散射中心在拉丝过程中的尺寸、分布和相态不易稳定控制;四是光纤的亮度、均匀性、柔韧性和耐热性难以同时兼顾

Benefits of technology

通过利用本申请的乳浊玻璃包层,并将乳浊玻璃包层与玻璃纤芯共拉丝为一体,而在玻璃纤芯的外表面形成了连续环形的乳浊玻璃包层,从而将导光功能和散射功能在径向上分离。在光传输过程中,玻璃纤芯主要承担轴向导光功能;部分高阶模式光、泄漏模式光以及芯包界面附近的倏逝场耦合光进入乳浊玻璃包层后,在散射相与玻璃基体的折射率不连续界面处发生散射,并通过乳浊玻璃包层与有机树脂涂层界面向外输出。由于散射相位于包层而非主要导光纤芯中,本发明能够在获得侧向出光的同时降低对轴向传输的过度削弱,减少了纤芯内强散射造成的传输损耗。散射相在乳浊玻璃包层内部原位形成,避免外表面刻蚀、沉积或粘附散射层带来的工艺复杂和可靠性问题。且在拉丝过程中的尺寸、分布和相态易于控制。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses an opaque glass cladding for side-emitting glass optical fibers, the side-emitting glass optical fiber itself, and a method for its fabrication. The opaque glass cladding is sleeved on the outside of the glass fiber core and is co-drawn integrally with the glass fiber core. A scattering phase is formed in situ within the opaque glass cladding; the scattering phase is at least one of a phase-separated region, a microcrystalline phase, or microbubbles. This application co-draws the opaque glass cladding integrally with the glass fiber core, forming a continuous annular opaque glass cladding on the outer surface of the glass fiber core. This radially separates the light guiding and scattering functions. This invention can achieve lateral light emission from the optical fiber while reducing excessive attenuation of axial transmission, thus reducing transmission loss caused by strong scattering within the fiber core.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of side-emitting optical fiber technology, specifically to an opaque glass cladding for side-emitting glass optical fiber, a side-emitting glass optical fiber, and a method for preparing the same. Background Technology

[0002] Side-emitting optical fibers can output light input from the end face along the length of the fiber from the side, and are widely used in automotive interiors, architectural contour lighting, landscape lighting, equipment status indication, flexible line light sources, and decorative lighting. Existing side-emitting optical fibers typically include polymer side-emitting fibers, multi-core glass side-emitting fibers, and quartz or glass-based side-emitting fibers.

[0003] Polymer-based side-emitting fibers are low-cost and easy to mold, but their heat resistance, weather resistance, and long-term dimensional stability are limited. They are prone to light decay, yellowing, cracking, or uneven light emission under high temperature, ultraviolet, humid, or prolonged bending environments. Multi-core glass-based side-emitting fibers have better heat resistance, but require complex bundled, arranged, and encapsulated processes. Light emission uniformity is significantly affected by the consistency of individual filaments and the interface state. Quartz or glass-based side-emitting fibers have good heat resistance and chemical stability, but their lateral light emission capability is limited if relying solely on a transparent core-cladding structure. Scattering structures are typically introduced into the core, cladding, or outer surface.

[0004] In existing technologies, common methods for introducing scattering structures include adding scattering particles to the fiber core, etching or roughening the outer surface of the fiber, depositing a scattering layer on the outer surface, inserting a rod containing scattering centers into a preform, or disrupting the light guiding conditions through an opening structure. While these methods can generate lateral light emission, they still have the following problems: First, scattering particles located in the fiber core can easily increase axial transmission loss, leading to a shorter transmission distance; second, the etching or deposition process on the outer surface increases manufacturing steps, and the reliability of the bonding between the scattering layer and the glass substrate is limited; third, the size, distribution, and phase of the scattering centers are difficult to control stably during the fiber drawing process; and fourth, it is difficult to simultaneously achieve optimal brightness, uniformity, flexibility, and heat resistance in optical fibers. Summary of the Invention

[0005] To overcome the above-mentioned shortcomings, the present invention aims to provide an opaque glass cladding for side-emitting glass optical fibers, a side-emitting glass optical fiber, and a method for preparing the same. The side-emitting glass optical fiber of the present invention has a simple structure, can be continuously drawn for manufacturing, has a stable and controllable scattering structure, and can balance lateral light emission intensity and optical transmission distance.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is an opaque glass cladding for a side-emitting glass fiber, characterized in that it is used to be sleeved on the outside of the glass fiber core and drawn together with the glass fiber core, and a scattering phase is formed in situ in the opaque glass cladding. The scattering phase is at least one of a phase-separated region, a microcrystalline phase, and microbubbles. The volume percentage of the in-situ formed scattering phase is 0.01% to 25%. The phase-separated region is formed by the scattering phase formed by the phase-separable glass during melting, annealing, heat treatment, or drawing. The average size of the scattering phase in the phase-separated region is 2 nm to 500 nm. The microcrystalline phase is formed by nucleating or crystallizing components, and the average size of the microcrystalline phase is 10 nm to 5 μm. The microbubbles are formed by controlling the glass composition, clarification process, atmosphere, redox state, or heat treatment process, and the average size of the microbubbles is 0.1 μm to 20 μm.

[0007] This application has the following beneficial effects: By utilizing the opaque glass cladding of this application and co-drawing the opaque glass cladding with the glass fiber core, a continuous annular opaque glass cladding is formed on the outer surface of the glass fiber core, thereby separating the light guiding and scattering functions radially. During light transmission, the glass fiber core mainly undertakes the axial light guiding function; some higher-order mode light, leakage mode light, and evanescent field coupled light near the core-cladding interface enter the opaque glass cladding and are scattered at the interface of the refractive index discontinuity between the scattering phase and the glass substrate, and output outward through the interface between the opaque glass cladding and the organic resin coating. Since the scattering phase is located in the cladding rather than in the main guiding fiber core, this invention can reduce excessive attenuation of axial transmission while obtaining lateral light output, reducing transmission loss caused by strong scattering within the fiber core. The scattering phase is formed in situ inside the opaque glass cladding, avoiding the process complexity and reliability problems caused by etching, deposition, or adhesion of the scattering layer on the outer surface. Moreover, its size, distribution, and phase state are easy to control during the drawing process.

[0008] Furthermore, the separable phase glass is selected from at least one of borosilicate opaque glass, aluminosilicate opaque glass, phosphosilicate opaque glass, fluoride opaque glass, or glass-ceramic opaque glass.

[0009] Furthermore, the opaque glass is a borosilicate opaque glass, comprising the following components in molar percentage: 50% to 85% SiO2, 5% to 30% B2O, 30% to 12% Al2O, and 0% to 18% Na2O and / or K2O.

[0010] Furthermore, the microcrystalline phase is obtained by adding nucleation or turbidity regulating components, which include at least one of the following components: TiO2, ZrO2, P2O5, BaO, CaF2, NaF, or LaF3.

[0011] Furthermore, the average size of the microbubbles is from 0.1 μm to 20 μm, and the microbubbles are formed using at least one of the following methods: A composite clarifying agent system is used to generate microbubbles in the opaque glass cladding: during glass melting, a composite clarifying agent system is used to generate microbubbles in the cladding, the composite clarifying agent system containing 0.3 wt% Na2SO4 and 0.05 wt% CeO2; Microbubbles are generated by adjusting the forming cooling regime or subsequent heat treatment regime: the formed and annealed glass block is placed in a high-temperature resistance furnace and heated to the foaming temperature range of 900℃ to 1100℃, and held at this temperature for 1 to 2 hours. Then it is cooled with the furnace. The peak temperature and holding time of the secondary heat treatment are controlled to form microbubbles.

[0012] Furthermore, the density of the scattering phase in the opaque glass cladding gradually increases along the direction from the input end to the output end. Therefore, by setting the density of the scattering phase to gradually decrease along the transmission direction of the optical fiber, the power attenuation caused by the input light propagating along the length direction at the end face can be compensated, thereby extending the effective transmission distance.

[0013] The present invention also provides a side-emitting glass fiber comprising the aforementioned opaque glass cladding. The opaque glass cladding is sleeved onto the outside of the glass fiber core and co-drawn with the glass fiber core to form a continuous annular opaque glass cladding integrally connected to it on the surface of the glass fiber core. The side-emitting glass fiber further includes an organic resin coating applied to the outer surface of the drawn opaque glass cladding. The thickness of the opaque glass cladding is 5 μm to 1000 μm, the diameter of the glass fiber core is 50 μm to 3000 μm, and the thickness of the organic resin coating is 5 μm to 500 μm.

[0014] The continuous annular opaque glass cladding of this invention serves both as an optical cladding for core-packet light guiding and as a scattering functional layer providing lateral light emission. This application utilizes an opaque glass cladding, which is also a glass matrix, enabling the formation of an inseparable scattering layer on the outer surface of the glass fiber core during fiber drawing. This results in high stability, and compared to the prior art method of forming the scattering layer through etching and deposition, the processing difficulty and cost are significantly reduced.

[0015] Furthermore, the refractive index n1 of the glass fiber core is greater than the effective refractive index n2 of the opaque glass cladding, and the refractive index n3 of the organic resin coating is greater than n2, with n1-n2 ranging from 0.001 to 0.080 and n3-n2 ranging from 0.001 to 0.200. According to optical principles, the design of n1>n2 allows the incident light to undergo total internal reflection at the interface between the fiber core and cladding, thus confining the light energy to the fiber core to the greatest extent possible and effectively increasing the light transmission length. When the light entering the opaque glass cladding reaches the interface of the organic resin coating after scattering, since the light travels from a low-refractive-index medium (n2) to a high-refractive-index medium (n3), the light easily penetrates the interface and escapes outwards, allowing the light energy to efficiently "leak" out from the side of the optical fiber, thereby achieving a long-distance, bright, and uniform side-emitting effect. Compared to optical fibers without this refractive index structure design, the light transmission distance of this invention is increased by 30%, and the brightness is increased by 10%.

[0016] Furthermore, this includes the following steps: STEP 01: Preparation steps of the glass core rod: The glass core is high-transmittance silicate glass, borosilicate glass, aluminosilicate glass, phosphate glass, or quartz glass; the difference in the coefficient of linear expansion between the opaque glass cladding and the glass core is no greater than 20 × 10⁻⁶. -7 / K, preferably not greater than 10×10 -7 / K; STEP 02: Preparation steps of the opaque glass cladding: A scattering phase is distributed in the opaque glass cladding; STEP 03: Co-drawing step: Insert the glass core rod into the cladding to form a core-cladding composite preform. Draw the glass at a temperature suitable for the common softening of the two types of glass. The drawing temperature is higher than the softening temperature of the glass core rod and the opaque glass cladding, and the glass core rod and the opaque glass cladding form a tight bonding interface during the drawing process. The drawing speed is 1 m / min to 2000 m / min. STEP 04: Organic Resin Layer Coating Step: An organic resin layer is coated onto the outer surface of the integral glass core and continuous annular opaque glass cladding obtained in step STEP 02. The refractive index n1 of the glass core is greater than the effective refractive index n2 of the opaque glass cladding, and the refractive index n3 of the organic resin coating is greater than n2. The organic resin coating is one or more of acrylic resin, silicone rubber, polyurethane, epoxy acrylate, fluorinated resin, or fluorine-free resin; preferably, the organic resin coating is a transparent or semi-transparent flexible coating. The organic resin coating imparts flexibility and environmental adaptability to the optical fiber, making it suitable for continuous line light source applications.

[0017] Furthermore, before or after step STEP 03, the method further includes a step of heat-treating the opaque glass cladding or the side-emitting glass fiber to control the size and volume fraction of the scattering phase. The heat treatment temperature is 0°C to 300°C above the glass transition temperature Tg of the opaque glass cladding, and the heat treatment time is 0.1 h to 100 h. The cladding with the scattering phase in step STEP 01 can be prepared by at least one of the following methods: Separable phase glass is used as the cladding material, and the cladding glass is melted, homogenized, annealed and then processed into a sleeve shape; Crystallizable opaque glass is used as the cladding material, and the cladding glass is melted, homogenized, annealed and then processed into a sleeve shape; By adjusting the melting atmosphere, amount of clarifying agent, redox state, forming cooling regime, or subsequent heat treatment regime of the opaque glass cladding, microbubbles with an average size of 0.1 μm to 20 μm are formed in the opaque glass cladding.

[0018] Furthermore, step STEP 01 also includes a density adjustment step for the scattering phase, so that the density of the scattering phase gradually increases along the direction from the light-incident end to the light-outceasing end. Attached Figure Description

[0019] Figure 1 This is a schematic diagram illustrating the fabrication process of a side-emitting optical fiber according to an embodiment of the present invention; Figure 2 This is a schematic diagram of the structure of a side-emitting optical fiber according to an embodiment of the present invention; Figure 3 This is a cross-sectional view of the side-emitting optical fiber in Embodiment 5 of the present invention.

[0020] In the picture, 1. Glass fiber core; 2. Opacity glass cladding; 21. Scattering phase; 3. Organic resin coating. Detailed Implementation

[0021] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby providing a clearer and more explicit definition of the scope of protection of the present invention.

[0022] In this patent, the refractive indices n1, n2, and n3 can be measured at 589 nm or at the center wavelength of the actual working light source. The refractive index n2 of the opaque glass cladding 2 is the equivalent refractive index, which can be measured by prism coupling, ellipsometrics, interferometry, or equivalent methods; for opaque glasses with multiphase structures, it can also be estimated by combining phase composition and volume fraction.

[0023] In this patent, the average size of the scattering phase 21 can be determined by transmission electron microscopy, scanning electron microscopy, optical microscopy, small-angle scattering, or image statistical methods. The volume fraction of the scattering phase 21 can be determined by image analysis, density method, microscopic statistics, or phase analysis methods.

[0024] The opaque glass cladding 2 of the present invention for side-emitting glass optical fiber is sleeved on the outside of the glass fiber core 1 and co-drawn integrally with the glass fiber core 1. A scattering phase 21 is formed in situ in the opaque glass cladding 2. The scattering phase 21 is at least one of a phase-separated region, a microcrystalline phase, and microbubbles. The volume percentage of the in-situ formed scattering phase 21 is 0.01% to 25%. In some embodiments, the volume percentage of the scattering phase 21 is 0.1% to 10%. The absolute value of the refractive index difference between the scattering phase 21 and the surrounding glass substrate is not less than 0.005, and in some embodiments, it is 0.01 to 0.20.

[0025] The phase-separated region is formed by the scattering phase 21 formed during the melting, annealing, heat treatment or drawing process of the phase-separable glass, and the average size of the phase-separated region is 2 nm to 500 nm. The microcrystalline phase is formed by nucleating or crystallizing components, and the average size of the microcrystalline phase is 10 nm to 5 μm. Microbubbles are formed by controlling the glass composition, clarification process, atmosphere, redox state, or heat treatment process, and the average size of the microbubbles ranges from 0.1 μm to 20 μm. Microbubbles are formed using at least one of the following methods: A composite clarifying agent system is used to generate microbubbles in the opaque glass cladding 2: During the glass melting process, a composite clarifying agent system is used to generate microbubbles in the cladding. The composite clarifying agent system contains 0.1wt%-1 wt% Na2SO4 and 0.01wt%-0.5wt% CeO2. This proportion of Na2SO4 and CeO2 helps prevent the formation of large bubbles during the melting and clarifying process, avoiding defects caused by excessively large or coalescing bubbles. In some embodiments, the composite clarifying agent system contains 0.1wt%-0.5wt% Na2SO4 and 0.01wt%-0.1wt% CeO2. By reducing the absolute amount of clarifying agent and combining it with a reducing atmosphere, the amount of gas generated can be significantly reduced. Before the bubbles rise and escape under buoyancy, their size is limited to between 0.1 μm and 5 μm, and they are uniformly dispersed in the glass matrix.

[0026] Microbubbles are generated by adjusting the forming cooling regime or subsequent heat treatment regime: The formed and annealed glass block is placed in a high-temperature resistance furnace and heated to a foaming temperature range above the glass transition temperature (Tg). It is held at this temperature for a certain time, and then cooled in the furnace. By controlling the peak temperature and holding time of the secondary heat treatment, the average size and volume fraction of the microbubbles can be adjusted. The higher the temperature and the longer the holding time, the larger the average size and the higher the volume fraction of the microbubbles. By controlling the peak temperature and holding time of the secondary heat treatment, the nucleation and growth kinetics of microbubbles can be perfectly controlled, thereby achieving effective control over the volume and number of microbubbles.

[0027] By using the two methods for generating microbubbles described above, the average size of the microbubbles can be precisely controlled within the range of 0.1μm to 20μm, and the volume ratio can be controlled within the target range of 0.01% to 25%, thus meeting the design requirements for brightness of different sides.

[0028] In some embodiments, the separable glass is selected from at least one of borosilicate opaque glass, aluminosilicate opaque glass, phosphosilicate opaque glass, fluoride opaque glass, or glass-ceramic opaque glass.

[0029] In some embodiments, the side-emitting glass fiber of the present invention includes the aforementioned opaque glass cladding 2. The opaque glass cladding 2 is sleeved on the outside of the glass fiber core 1 and drawn together with the glass fiber core 1 to form a continuous annular opaque glass cladding 2 integrally connected to it on the surface of the glass fiber core 1. The side-emitting glass fiber also includes an organic resin coating 3 coated on the outer surface of the drawn opaque glass cladding 2. The thickness of the opaque glass cladding 2 is 5 μm to 1000 μm, the diameter of the glass fiber core 1 is 50 μm to 3000 μm, and the thickness of the organic resin coating 3 is 5 μm to 500 μm.

[0030] In this invention, the "continuous annular opaque glass cladding" refers to a cladding layer that is an inorganic glass layer continuously distributed circumferentially around the glass fiber core 1, rather than a discrete particle coating layer, an outer surface roughening layer, an inlaid rod, or a locally perforated structure. This cladding layer serves both as an optical cladding layer participating in core-packet light guiding and as a scattering functional layer providing lateral light emission. This application utilizes an opaque glass cladding 2, which is also a glass matrix, enabling the formation of an inseparable scattering layer on the outer surface of the glass fiber core 1 during fiber drawing. This results in high stability, and compared to the prior art method of forming the scattering layer through etching and deposition, the processing difficulty and cost are greatly reduced.

[0031] In some implementations, glass core rods and cladding glass with the same softening temperature range are used, and after the two are joined together, they are co-drawn, with the co-drawing temperature being higher than the softening temperature.

[0032] In some embodiments, the refractive index n1 of the glass fiber core 1 is greater than the effective refractive index n2 of the opaque glass cladding 2, and the refractive index n3 of the organic resin coating 3 is greater than n2, with n1-n2 ranging from 0.001 to 0.080 and n3-n2 ranging from 0.001 to 0.200.

[0033] The following explanation uses borosilicate opaque glass as an example of a separable glass. A schematic diagram of the fabrication process for the side-emitting optical fiber is shown below. Figure 1 As shown: Example 1: Fabrication of two-sided light-emitting optical fiber with borosilicate phase-separated opaque glass cladding: ① High transmittance borosilicate glass was selected as the glass core material, and the refractive index n1 of the core was 1.47 to 1.58.

[0034] ② Preparation steps of opaque glass cladding 2: Select separable borosilicate glass as cladding material. The basic composition of the cladding includes, by molar percentage: 50% to 85% SiO2, 35% to 30% B2O, 30% to 12% Al2O, 0% to 18% Na2O and / or K2O, and may further contain one or more of CaO, BaO, ZnO, and P2O5.

[0035] In some embodiments, the molar percentage of the cladding base composition is: SiO2 52%-65%, B2O3 18%-25%, Al2O3 3%-8%, Na2O 0-12%, K2O 0-12%, CaO 0-5%, BaO 0-8%, ZnO 0-5%.

[0036] The cladding glass is melted, homogenized, and annealed before being processed into a sleeve. By adjusting the SiO2 / B2O3 ratio, the alkali metal oxide content, and the heat treatment regime, the cladding glass forms a silicon-rich phase and a boron-rich phase separation structure. The average thickness of the phase separation region is controlled between 2 nm and 500 nm, preferably between 5 nm and 200 nm.

[0037] ③ Insert the glass core rod into the cladding to form a core-clad composite preform, and draw it into wire at a temperature suitable for the common softening of the two types of glass (glass core rod and cladding glass).

[0038] Taking a cladding with a molar percentage composition of 65 mol% SiO2, 20 mol% B2O3, 3 mol% Al2O3, and 12 mol% Na2O as an example, its softening temperature is 750℃-830℃. At the same time, a mandrel with a softening temperature within this range is selected, and the two are nested together and drawn at 870-920℃.

[0039] Taking the cladding composition of 58 mol% SiO2, 25 mol% B2O3, 6 mol% Al2O3 as an example, and 6 mol% Na2O, 5 mol% CaO as an example, its softening temperature is 730-820℃. At the same time, a mandrel with a softening temperature within this range is selected, and the two are nested together and drawn at 860-900℃.

[0040] Taking a cladding with a molar percentage composition of 52 mol% SiO2, 18 mol% B2O3, 8 mol% Al2O3, 10 mol% K2O, 8 mol% BaO, and 4 mol% ZnO as an example, its softening temperature is 610–680℃. At the same time, a mandrel with a softening temperature within this range is selected, and the two are nested together and drawn at 710–800℃.

[0041] ④ After drawing, the optical fiber is coated with organic resin online and cured. First, the drawn optical fiber is passed through a coating cup to uniformly coat the glass surface with liquid resin. Then, it enters an ultraviolet curing oven or a thermal curing channel to rapidly cross-link and cure the resin to form a protective layer. Specific process conditions and temperature parameters are as follows: the coating temperature is controlled between 40℃ and 60℃; curing is performed using ultraviolet light irradiation with an intensity set to 800 to 1200 mW / cm²; and the curing time is controlled between 0.5 and 2 seconds to ensure complete hardening of the coating without any residual bubbles, thus obtaining the side-emitting optical fiber of this invention (e.g., ...). Figure 2 (As shown). The organic resin coating is one or more of acrylate resin, silicone rubber, polyurethane, epoxy acrylate, fluorinated resin, or fluorine-free resin. In some embodiments, the organic resin coating is a transparent or translucent flexible coating.

[0042] A side-emitting glass fiber with a glass core 1, a continuous annular opaque glass cladding 2, and an organic resin coating 3 is obtained by drawing. In this embodiment, the refractive index (n1) of the glass core 1 is greater than the effective refractive index (n2) of the opaque glass cladding 2, and the refractive index (n3) of the organic resin coating 3 is greater than n2.

[0043] Example 2: Glass-ceramic opacified cladding side-emitting optical fiber containing microcrystalline phase This embodiment is basically the same as Embodiment 1, except that the cladding is made of crystallizable opaque glass, which also contains one or more of TiO2, ZrO2, P2O5, BaO, CaF2, NaF, and LaF3 as nucleation or opacification control components.

[0044] In some embodiments, the molar percentage of the cladding composition is: 68 mol% SiO2, 15 mol% B2O3, 4 mol% Al2O3, 8 mol% Na2O, 2 mol% CaO, 2 mol% TiO2, and 1 mol% ZrO2.

[0045] In some embodiments, the molar percentage of the cladding composition is: 60 mol% SiO2, 22 mol% B2O3, 5 mol% Al2O3, 6 mol% Na2O, 3 mol% K2O, 2 mol% BaO, and 2 mol% P2O5.

[0046] In some embodiments, the molar percentage of the cladding composition is: 55 mol% SiO2, 20 mol% B2O3, 8 mol% Al2O3, 10 mol% Na2O, 4 mol% CaO, 2 mol% CaF2, and 1 mol% ZrO2.

[0047] Through melting, forming, and controlled heat treatment, microcrystalline phases with an average size of 10 nm to 5 μm are precipitated in the cladding glass. The specific treatment method is as follows: First, the cladding glass raw materials are mixed evenly and then melted at a high temperature of 1450℃ to 1550℃ for 3 to 5 hours to ensure that the raw materials are completely melted and uniform. Then, the temperature is lowered to 50℃ to 80℃ above the glass transition point and held for 2 hours to eliminate internal stress. After that, the temperature is raised to 620℃ to 750℃ and held for 1 to 4 hours for controlled crystallization treatment. The precipitation size and volume fraction of the microcrystalline phase are controlled by adjusting the holding temperature and holding time. Then, the crystallized glass is processed into a sleeve. The subsequent core rod assembly, wire drawing, coating and curing steps are exactly the same as in Example 1. Finally, a glass-ceramic opaque cladding side-emitting optical fiber with uniform microcrystalline phase scattering centers is obtained. The obtained microcrystalline phase is uniformly distributed and can stably provide side scattering effect. Moreover, the chemical stability and heat resistance of the glass-ceramic cladding are further improved compared with the phase-separated opaque cladding. By controlling the heat treatment temperature and time, the size and volume fraction of the microcrystalline phase can be adjusted, thereby regulating the lateral light emission intensity and transmission distance. In this embodiment, the refractive index (n1) of the glass core 1 is greater than the effective refractive index (n2) of the opaque glass cladding 2, and the refractive index (n3) of the organic resin coating 3 is greater than n2.

[0048] Example 3: Side-emitting optical fiber with a controllable microbubble-containing opaque glass cladding 2 This embodiment is basically the same as Embodiment 1, except that the cladding also contains microbubbles with an average size of 0.1 μm to 20 μm. The microbubbles can be adjusted by the glass melting atmosphere, the amount of clarifying agent, the redox state, the forming cooling regime, or the subsequent heat treatment regime. The large refractive index difference between the microbubbles and the glass matrix provides significant scattering at a low volume fraction.

[0049] In some embodiments, during glass melting, a composite clarifying agent system is used to generate microbubbles in the cladding. This system comprises 0.3 wt% Na₂SO₄ and 0.05 wt% CeO₂, where sodium sulfate decomposes at 1300°C–1400°C, releasing SO₂ and O₂, and CeO₂ releases O₂ above 1200°C. By reducing the absolute amount of clarifying agent used and combining it with a reducing atmosphere, the amount of gas generated can be significantly reduced, avoiding the formation of large bubbles at the millimeter scale. The released trace amounts of gas are present when the glass melt viscosity is approximately 10. 2 ~10 3 At Pa·s, tiny bubble nuclei are formed. Due to the small amount of gas, the size of the bubbles is limited to between 0.1 μm and 5 μm before they rise and escape under the action of buoyancy, and they are uniformly dispersed in the glass matrix.

[0050] In some embodiments, the shaped and annealed glass block is placed in a high-temperature resistance furnace and heated to a foaming temperature range of 900°C to 1100°C at a heating rate of 3–5°C / min, and held at this temperature for 1–2 hours, followed by furnace cooling. By precisely controlling the peak temperature and holding time of the secondary heat treatment, the nucleation and growth kinetics of microbubbles can be perfectly controlled. Holding at 1000°C for 1 hour can generate bubbles of approximately 1–5 μm, while holding at 1100°C for 2 hours can generate bubbles of 5–20 μm.

[0051] To avoid excessive scattering causing a significant decrease in axial transmission distance, the volume fraction of microbubbles is preferably controlled to be 0.01% to 5%, more preferably 0.05% to 2%.

[0052] When the bubble size is 0.1~0.5μm, which is smaller than or close to the wavelength of light, light encountering these tiny bubbles primarily undergoes Rayleigh scattering, and the scattered light is relatively uniformly distributed in all directions. Due to the small scattering cross-section, the light transmission along the fiber axis is less obstructed, resulting in relatively low transmission loss. This type of fiber is more suitable for uniform light source applications with longer transmission distances. When the bubble size reaches 5~10μm, its size is larger than or much larger than the wavelength of visible light. At this point, the interaction between the light and the bubble transforms into Mie scattering. Mie scattering has a large scattering cross-section, and its ability to deflect and extract light is far stronger than Rayleigh scattering. Strong Mie scattering leads to a large amount of light energy being extracted over extremely short distances, causing a sharp increase in transmission loss. This type of fiber is suitable for short-distance, high-brightness side-emitting scenarios. If the bubble size is larger than 20μm, this fiber essentially loses its practical value as a "uniform side-emitting light source."

[0053] In this embodiment, the refractive index (n1) of the glass fiber core 1 is greater than the effective refractive index (n2) of the opaque glass cladding 2, and the refractive index (n3) of the organic resin coating 3 is greater than n2.

[0054] Example 4: Color-enhanced side-emitting optical fiber containing luminescent ions In any of the opaque glass cladding systems in Examples 1 to 3, Eu was further added. 3+ 、Tb 3+ Dy 3+ Ce 3+ Mn 2+ One or more luminescent ions are present, wherein the amount of luminescent ions added is 0.001% to 2% of the cladding glass mass based on the amount of oxides added. Among them, Eu... 3+ It can be used for red light enhancement, Tb 3+ It can be used for green light enhancement, Dy 3+ It can be used for yellow-white light emission adjustment, Ce 3+ It can be used for luminescence modulation under blue-violet excitation, Mn 2+ It can be used to adjust orange-red or green light emission.

[0055] In some embodiments, the molar percentage composition of the cladding is: 52 mol% SiO2, 18 mol% B2O3, 8 mol% Al2O3, 10 mol% K2O, 8 mol% BaO, 4 mol% ZnO, plus Dy 3+ (0.2wt% of glass mass).

[0056] In some embodiments, the cladding formulation comprises the following molar percentages: 55 mol% SiO2, 20 mol% B2O3, 8 mol% Al2O3, 10 mol% Na2O, 4 mol% CaO, 2 mol% CaF2, 1 mol% ZrO2, and added Ce. 3+ + Tb 3+ (Each accounts for 0.1wt% of the glass mass).

[0057] The luminescent ions are used as color conversion or luminescence enhancement components in conjunction with the phase-separated phase region, microcrystalline phase, or microbubble scattering phase 21. The luminescent ions are not the sole necessary condition for achieving lateral light emission in this invention, but rather serve as an optional means of color and brightness adjustment.

[0058] Example 5: Scattering intensity gradient modulation along the length of the contralateral light-emitting fiber In applications requiring long-distance uniform line light sources, the density of the scattering phase 21 in the opaque glass cladding 2 can be made to increase along the fiber length. This can be achieved by altering the composition of the opaque glass cladding along its length, the heat treatment temperature gradient, the heat treatment time gradient, or by secondary local heat treatment. The density of the scattering phase 21 is lower near the light-incident end and higher further away, compensating for the power attenuation caused by the propagation of the input light along its length at the end face. (See attached image.) Figure 3As shown, the refractive index of the opaque glass cladding 2 of the side-emitting optical fiber in this embodiment exhibits a gradient increase along the direction from the light-inlet end to the light-outlet end of the optical fiber.

[0059] In some implementations, the scattering intensity gradient of the glass sleeve is controlled using the following method: In the annealing furnace beneath the fiber drawing tower, a precise temperature gradient is established along the fiber axis (length direction). The annealing temperature near the input end is set slightly above the glass transition temperature (Tg) (e.g., Tg + 20°C), allowing only a small amount of microphase separation. As the fiber extends further, the annealing furnace temperature increases in a gradient of 2-5°C / m, with the temperature at the far end rising to Tg + 60°C or even higher. The temperature gradient method of this invention offers extremely high process continuity. The high-temperature region not only accelerates the diffusion of the nucleating agent but also significantly promotes the growth of microbubbles or microcrystals, resulting in a simultaneous increase in the size and density of the scattering phase 21 in the far-end region, thereby achieving an increase in scattering intensity.

[0060] In other possible implementations, the scattering intensity gradient of the glass sleeve can be controlled by employing a multi-temperature zone tube furnace during the secondary heat treatment process after optical fiber drawing. The optical fiber is passed through the furnace chamber at a constant speed (e.g., 5-10 m / min). By adjusting the length and heating power of each temperature zone within the furnace chamber, the time the optical fiber spends passing through the effective crystallization temperature zone at the incident end is reduced to only 10-20 seconds, while the time spent passing through the same temperature zone at the distal end is extended to 60-120 seconds. The longer holding time allows sufficient time for the micro-phase droplets or microcrystals inside the glass at the distal end to undergo Ostwald ripening, thereby forming larger and denser scattering centers.

[0061] Comparative Example A: Comparison of the refractive indices of different glass fiber cores 1, opaque glass cladding 2, and organic resin coatings 3: The refractive indices of the glass fiber core 1, opaque glass cladding 2, and organic resin coating 3 in the aforementioned embodiments 1-3 were set according to the following conditions: the refractive index (n1) of the glass fiber core 1 was greater than the effective refractive index (n2) of the opaque glass cladding 2, and the refractive index (n3) of the organic resin coating 3 was greater than n2. The optical fiber performance under different refractive index conditions was compared, and the results are shown in Table 1.

[0062] Based on optical principles, the n1>n2 design allows for total internal reflection of the incident light at the core-cladding interface, confining the light energy to the core to the maximum extent and effectively increasing the transmission length. When the light entering the opaque glass cladding 2 reaches the organic resin coating 3 interface after scattering, it easily penetrates the interface and escapes outwards from the high-refractive-index medium (n3), allowing light energy to efficiently "leak" out from the side of the optical fiber. This achieves long-distance, bright, and uniform side-emitting light. Experimental data shows that compared to optical fibers without this refractive index structure design, the transmission distance of this invention is increased by 30%, and the brightness is increased by 10%.

[0063] The optical transmission distance is calculated as follows: an end-to-end loss test is performed using a light source and an optical power meter. That is, a light source with known power is input into one end of the optical fiber, and the received optical power is measured at the other end. The difference between the two is the total loss, and the effective optical transmission distance of the optical fiber can be calculated from this.

[0064] Table 1. Comparison of the impact of different refractive indices of fiber layers on the performance of side-emitting fibers.

[0065] As can be seen from Comparative Example 1, if n1 > n2 > n3, although the light transmission distance can be significantly increased, the unit brightness is significantly reduced, thus greatly negatively impacting the side-emitting effect. If n1 < n2 < n3 (Comparative Example 2), the brightness can be significantly increased, but the light transmission distance is significantly shortened. If n1 < n2 = n3, most of the optical fiber will enter the opaque glass cladding 2 from the fiber core and exit directly from the interface of the organic resin coating 3, resulting in higher brightness, but the light transmission distance is significantly shortened because most of the light from the fiber core is emitted. Therefore, by precisely controlling the refractive index of each layer, a high-low-high gradient refractive index is constructed for the glass fiber core 1, opaque glass cladding 2, and organic resin coating 3 in this application. This ensures sufficient unit brightness and achieves an ideal light transmission distance, balancing the side-emitting effect and the light transmission distance, and simultaneously realizing the effects of increased brightness and increased light transmission distance.

[0066] Comparative Example B: Comparison of the formation modes of scattering phase 21 Comparative Example 4 shows the preparation of scattering phase 21 on an optical fiber core using existing deposition or etching methods, and its performance is compared with that of the side-emitting optical fiber obtained in this invention. The results are shown in Table 2. Table 2. Performance Comparison of the Side-Emitting Fiber of the Present Invention with that of the Existing Side-Emitting Fiber

[0067] The specific steps for etching the outer surface of the fiber core to form a scattering layer in Comparative Example 4 are as follows: First, the high-purity glass core rod is cleaned and polished to remove surface stains and processing damage; then, a hydrofluoric acid-based etching solution is used to perform wet chemical etching on the outer surface of the fiber core. By controlling the concentration of the etching solution, the etching temperature, and the etching time, randomly distributed micron-sized pits are etched on the outer surface of the fiber core to form a rough scattering interface; after etching, the fiber core is repeatedly rinsed with deionized water to remove residual etching products on the surface, and after drying, a fiber core with a scattering layer is obtained. Finally, the fiber core is assembled with a sleeve and drawn to produce a side-emitting optical fiber.

[0068] The typical process steps of Comparative Example 5 are as follows: First, the high-purity glass core rod is cleaned and polished to ensure the cleanliness of the substrate surface; second, particles or scattering layers with scattering characteristics are uniformly deposited on the surface of the core rod using a deposition process; then, the treated core rod is nested and assembled with the selected outer cladding glass tube to form a side-emitting fiber preform; finally, the preform is placed in a drawing tower for high-temperature heating and drawing to prepare the finished side-emitting fiber.

[0069] As can be seen from Table 2, the method of forming a scattering phase in situ in the opaque glass cladding of this application has both a longer light transmission distance and higher brightness. Moreover, the scattering phase is stably bonded to the glass fiber core, and the scattering phase still maintains high dispersion uniformity after drawing, ensuring that the side-emitting fiber has high performance stability.

[0070] The above embodiments are only for illustrating the technical concept and features of the present invention. Their purpose is to enable those skilled in the art to understand the content of the present invention and implement it. They should not be used to limit the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. An opaque glass cladding for a side-emitting glass optical fiber, characterized in that, Used to be sleeved on the outside of the glass fiber core and drawn integrally with the glass fiber core, a scattering phase is formed in situ in the opaque glass cladding. The scattering phase is at least one of phase-separated regions, microcrystalline phases, and microbubbles, and the volume percentage of the in-situ formed scattering phase is 0.01% to 25%. The phase-separated region is formed by a scattering phase formed during the melting, annealing, heat treatment or wire drawing process of the phase-separable glass, and the average size of the scattering phase in the phase-separated region is 2 nm to 500 nm. The microcrystalline phase is formed by nucleating or crystallizing components, and the average size of the microcrystalline phase is 10 nm to 5 μm. The microbubbles are formed by controlling the glass composition, clarification process, atmosphere, redox state, or heat treatment process, and the average size of the microbubbles is 0.1 μm to 20 μm.

2. The opaque glass cladding according to claim 1, characterized in that, The separable phase glass is selected from at least one of borosilicate opaque glass, aluminosilicate opaque glass, phosphosilicate opaque glass, fluoride opaque glass, or glass-ceramic opaque glass.

3. The opaque glass cladding according to claim 2, characterized in that, The opaque glass is a borosilicate opaque glass, comprising the following components by molar percentage: 50% to 85% SiO2, 5% to 30% B2O, 30% to 12% Al2O, and 0% to 18% Na2O and / or K2O.

4. The opaque glass cladding according to claim 3, characterized in that, The microcrystalline phase is obtained by adding nucleation or opacification regulating components, which include at least one of the following components: TiO2, ZrO2, P2O5, BaO, CaF2, NaF or LaF3.

5. The opaque glass cladding according to claim 1, characterized in that, The microbubbles have an average size of 0.1 μm to 20 μm and are formed using at least one of the following methods: Microbubbles are generated in the opaque glass cladding using a composite clarifying agent system: During glass melting, microbubbles are generated in the cladding using a composite clarifying agent system containing Na2SO4 and CeO2. Microbubbles are generated by adjusting the forming cooling regime or subsequent heat treatment regime: the formed and annealed glass block is placed in a high-temperature resistance furnace, heated to the foaming temperature range, and held at this temperature for 1 to 2 hours, and then cooled with the furnace. The peak temperature and holding time of the secondary heat treatment are controlled to form microbubbles.

6. The opaque glass cladding according to any one of claims 1-5, characterized in that, The density of the scattering phase in the opaque glass cladding gradually increases along the direction from the incident end to the emitting end.

7. A side-emitting glass optical fiber, characterized in that, The optical fiber comprises an opaque glass cladding as described in any one of claims 1-6, wherein the opaque glass cladding is sleeved on the outside of the glass fiber core and drawn together with the glass fiber core to form a continuous annular opaque glass cladding integrally connected thereto on the surface of the glass fiber core. The side-emitting glass fiber further comprises an organic resin coating coated on the outer surface of the drawn opaque glass cladding. The thickness of the opaque glass cladding is 5 μm to 1000 μm, the diameter of the glass fiber core is 50 μm to 3000 μm, and the thickness of the organic resin coating is 5 μm to 500 μm.

8. The side-emitting glass optical fiber according to claim 7, characterized in that, The refractive index n1 of the glass fiber core is greater than the effective refractive index n2 of the opaque glass cladding, and the refractive index n3 of the organic resin coating is greater than n2, n1-n2 is 0.001 to 0.080, and n3-n2 is 0.001 to 0.

200.

9. The method for preparing the side-emitting glass optical fiber according to claim 7 or 8, characterized in that, Includes the following steps: STEP 01: Preparation steps of the glass core rod: The glass core is high-transmittance silicate glass, borosilicate glass, aluminosilicate glass, phosphate glass, or quartz glass; the difference in the coefficient of linear expansion between the opaque glass cladding and the glass core is no greater than 20 × 10⁻⁶. -7 / K; STEP 02: Preparation steps of the opaque glass cladding: A scattering phase is distributed in the opaque glass cladding; STEP 03: Co-drawing step: Insert the glass core rod into the cladding to form a core-cladding composite preform. Draw the glass at a temperature suitable for the common softening of the two types of glass. The drawing temperature is higher than the softening temperature of the glass core rod and the opaque glass cladding, and the glass core rod and the opaque glass cladding form a tight bonding interface during the drawing process. The drawing speed is 1 m / min to 2000 m / min. STEP 04: Organic resin coating step: Coat the outer surface of the integral glass core and continuous annular opaque glass cladding obtained in step STEP 02 with an organic resin layer. The refractive index n1 of the glass core is greater than the effective refractive index n2 of the opaque glass cladding, and the refractive index n3 of the organic resin coating is greater than n2.

10. The method for preparing a side-emitting glass optical fiber according to claim 9, characterized in that, Before or after step STEP 03, the method further includes heat treatment of the opaque glass cladding or the side-emitting glass fiber to control the size and volume fraction of the scattering phase. The heat treatment temperature is 0°C to 300°C above the glass transition temperature Tg of the opaque glass cladding, and the heat treatment time is 0.1 h to 100 h. The cladding with the scattering phase in step STEP 01 can be prepared by at least one of the following methods: Separable phase glass is used as the cladding material, and the cladding glass is melted, homogenized, annealed and then processed into a sleeve shape; Crystallizable opaque glass is used as the cladding material, and the cladding glass is melted, homogenized, annealed and then processed into a sleeve shape; By adjusting the melting atmosphere, amount of clarifying agent, redox state, forming cooling regime, or subsequent heat treatment regime of the opaque glass cladding, microbubbles with an average size of 0.1 μm to 20 μm are formed in the opaque glass cladding.